Hazard identification and the prevalence of occupational skin disease in Indonesian Batik workers - Sri Awalia Febriana; Yohanes Ridora; Niken Indrastuti; Kusuma Dewi; Erdina; Katharina Oginawati; Ikeu Tanziha; Cita Rosita Sigit Prakoeswa; Fajar Waskito; Marie-Louise Schuttelaar (Scientific Reports, 2023)
Abstract Batik, a resist-dyeing technique to decorate a special cotton fabric, has been practiced for centuries in Indonesia. Unfortunately, as an informal enterprise, batik industry activities lack work safety and health regulations. This study aimed to identify potential health hazards, including inventorying the chemicals to which the workers are exposed, the PPE profile, and investigating the prevalence of occupational skin diseases (OSD) in the batik industry. A cross-sectional study and an inventory of exposure to the chemicals were done in traditional batik workplaces in 5 districts in Yogyakarta province, Indonesia. The chemicals were classified as potential sensitizers/irritants, and the workers were examined and interviewed using the Nordic Occupational Skin Questionnaire-2002/LONG. Of 222 traditional batik workers, OSD were diagnosed in 61 (27.5%) workers, with occupational contact dermatitis was the most common OSD encountered (n = 23/61; 37.7%) (allergic contact dermatitis n = 7/23; irritant contact dermatitis n = 16/23). A smaller portion of other OSD was also encountered including callus, miliaria, and nail disorder (9%, 6.3%, and 5.9%, respectively). During each step of the traditional batik manufacturing process, the workers are exposed to substances that act as irritants and/or as potential contact allergens. However, only one-fourth of the workers used PPE regularly, particularly during the coloring process and wax removal (wet processes). Traditional batik manufacturing process exposes the worker to various physical and chemical hazards, resulting in a high prevalence of occupational skin diseases, especially contact dermatitis among the employees.